Experimental and numerical analysis of the spray characteristics of biodiesel–ethanol fuel blends. (October 2021) - Geng, Limin; Xie, Yuantao; Wang, Jue; Liu, Wenchuan; Li, Chong; Wang, Cheng
The effects of adding ethanol on the macroscopic and microscopic spray characteristics of biodiesel were investigated by experimental and numerical methods. The spray tip penetration (STP) was recorded with a high-speed camera system, while the statistical size distribution of atomized droplets and the Sauter mean diameter (SMD) were obtained using a Malvern laser particle size analyzer. The spray calculation models were established with Fluent software, and the calculation results were validated by the experimental results. Then the numerical simulation of the spray characteristics for diesel, biodiesel, and biodiesel–ethanol fuel blends were conducted. The results showed that the farther the distance is from the nozzle exit, the lower the concentration and the velocity of atomized droplets. The concentration and the velocity of atomized droplets gradually decrease along the radial direction, extending from the center to the periphery. The turbulent kinetic energy (TKE) at the front and rear of the spray is relatively lower, while the TKE is higher in the middle of the spray, and turbulent vortices appear on both sides of the axial spray center. In addition, the spray characteristics of the different fuels revealed that compared to diesel, the STP and SMD of biodiesel increase by 33.59% and 33.08% on average, respectively. The maximum concentration of biodiesel is higher than that of diesel, and the concentration distribution is more concentrated. The droplet velocity and TKE of biodiesel respectively decrease by 7.38% and 14.49% in comparison to diesel. When ethanol was added to biodiesel by a volume percentage of 30%, the STP and SMD of biodiesel–ethanol fuel blends reduce by 22.05% and 20.88%, respectively. The concentration distribution, the velocity distribution, and the TKE distribution of the fuel blends are similar to that of diesel. This indicates that adding 30% ethanol to biodiesel can effectively improve its spray quality.